Killer instinct - Patterson, James, 1947-; Roughan, Howard (New York : Little Brown and Company, 2019)
The murder of an Ivy League professor pulls Dr. Dylan Reinhart out of his ivory tower and onto the streets of New York, where he reunited with his old partner, Detective Elizabeth Needham. As the worst act of terror since 9/11 strikes the city, a name on the casualty list rocks Dylan's world. Is his secret past about to be brought to light?
Sequel to Instinct.
Keywords: Policewomen -- New York (State) -- New York -- Fiction; College teachers -- New York (State) -- New York -- Fiction; Murder -- Investigation -- Fiction; Terrorism -- Fiction; New York (N.Y.) -- Fiction; Large type books; Detective and mystery fiction; Thrillers (Fiction)